Mitoxantrone and acquired Long-QT Syndrome. Case presentation. - Brandy Viera Valdés; Lázaro Enrique De la Cruz Aviléz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
The acquired Long-QT Syndrome can be caused by more than 100 non anti-arrhythmic drugs. These drugs block potassium channels; particularly the IKr which extends the ventricular repolarization beyond 450 ms. This syndrome is associated with ventricular helical tachycardia that could potentially cause immediate death. We report a patient with diagnosis of leukaemia who was treated with mitoxantrone and presented syncope. The electrocardiogram showed an interval QTc of 576 ms. After an exclusion diagnosis we concluded that there could be an association with the use of this drug caused by its toxic effects for the cardiac system. Mitoxantrone interferes in ionic transportation through cellular membrane, delays the exit of potassium from the cells and acts in the functioning of ATP asa Na/K altering the ventricular repolarization; however, it is not on the list of drugs that enlarge the QT interval. Our objective with this work is to raise the interest on new reports on this subject, and to establish a more direct causal relation through the evidence derived from new experiences.